(untitled) (Al-Academy, 2019)
The topic of research (women and ideology in the feature film) is a series of researches addressed by the researcher on the subject of women in the feature film through studying the ideology as a thought and political system not only limited to the world of men, but women had a significant contribution in this area. The research identified the problem and its need as well as the objectives of the research and clarified its limits and importance. The research also identified the theoretical framework, which included the following axes: personality and ideology, film and ideology, then women and ideology in the film. After the completion of the theoretical framework, the research concluded a set of indicators of the theoretical framework that were adopted as a tool to analyze the sample. The research procedures consisted of analyzing the research sample which is a film (Frida, screenplay: Eba Arvat and Julia Taymor and directed by Julia Taymor) listing the results of the analysis and conclusions followed by a list of sources and margins